Locating sensory labyrinth theatre within immersive theatres' history. Issue 2 (3rd May 2020) - Howson-Griffiths, Teri
ABSTRACT: Immersive theatres have emerged since the turn of the millennium as a popular form of performance. Intricate and elaborate, they interweave playfulness into the relationship between performer, audience, and performance space. Discussion of immersive theatres has largely focussed on a selection of urban theatre companies who have acquired reputations as the forerunners in the field. On the periphery, other practitioners and companies have been developing immersive methodologies within theatre that are, as yet, largely undocumented within this scholarship. This paper contributes to the widening of this discussion by considering the work of Iwan Brioc and his sensory labyrinth theatre (s.l.t). It explores s.l.t within the context of North Wales, referencing its influences from Columbian theatre director Enrique Vargas's work on the 'poetics of the senses'. In doing so, it expands the current conceptualisation of immersive theatres, and in broadening the work being examined within this field, focuses on the transformative potential of the work discussed